Methamphetamine-associated pulmonary arterial hypertension. Issue 5 (16th September 2022) - Kolaitis, Nicholas A.; Saggar, Rajan; De Marco, Teresa
Abstract : Purpose of review: Methamphetamine use is increasing in popularity globally, and chronic users suffer from various drug toxicities, including the development of pulmonary arterial hypertension. Although it was previously thought to be a possible cause of pulmonary arterial hypertension, as of the sixth World Symposium on Pulmonary Hypertension, methamphetamine use is now recognized as a definite cause of pulmonary arterial hypertension. This review will discuss the history of methamphetamine use, the link between methamphetamine use and pulmonary arterial hypertension, and the clinical characteristics of patients with pulmonary hypertension from methamphetamine use. Recent findings: The mechanism by which methamphetamine abuse leads to pulmonary hypertension is unclear. However, recent studies have suggested that reduced expression of carboxylesterase 1 may be implicated due to maladaptation to the environmental injury of methamphetamine abuse. Based on the report of two recent cohort studies, patients with methamphetamine-associated pulmonary arterial hypertension have a worse functional class, less favorable hemodynamics, impaired health-related quality of life, increased health-care utilization, and attenuated survival, as compared to those with idiopathic pulmonary arterial hypertension. Summary: Future studies are needed to better understand the mechanism by which methamphetamine use leads to pulmonary arterial hypertension. Methamphetamine-associated pulmonary arterial hypertension likely represents a more advanced disease state than idiopathic pulmonary arterial hypertension, however, it is treated less aggressively in clinical practice.